The timing of introduction of pharmaceutical innovations in seven European countries. Issue 4 (22nd April 2014) - Westerling, Ragnar; Westin, Marcus; McKee, Martin; Hoffmann, Rasmus; Plug, Iris; Rey, Grégoire; Jougla, Eric; Lang, Katrin; Pärna, Kersti; Alfonso, José L.; Mackenbach, Johan P.
Abstract Rationale, aims and objectives Differences in the performance of medical care may be due to variation in the introduction and diffusion of medical innovations. The objective of this paper is to compare seven European countries (United Kingdom, the Netherlands, West Germany, France, Spain, Estonia and Sweden) with regard to the year of introduction of six specific pharmaceutical innovations (antiretroviral drugs, cimetidine, tamoxifen, cisplatin, oxalaplatin and cyclosporin) that may have had important population health impacts. Methods We collected information on introduction and further diffusion of drugs using searches in the national and international literature, and questionnaires to national informants. We combined various sources of information, both official years of registration and other indicators of introduction (clinical trials, guidelines, evaluation reports, sales statistics). Results and conclusions The total length of the period between first and last introduction varied between 8 years for antiretroviral drugs and 22 years for cisplatin. Introduction in Estonia was generally delayed until the 1990s. The average time lags were smallest in France (2.2 years), United Kingdom (2.8 years) and the Netherlands (3.5 years). Similar rank orders were seen for year of registration suggesting that introduction lags are not only explained by differences in the process of registration. We discuss possible reasons for these between‐country differences and implications for the evaluation of medical care.